Effectiveness, Efficiency and Instruction Appeal of Blended Learning Model - Djoko Dwiyogo, Wasis; Ligya Radjah, Carolina (International Journal of Psychosocial Rehabilitation, 2020)
The practice of learning to acquire success has so far been measured by the level of effectiveness with a percentage range from 0% to 100% and converted into values E to A. While in the science of knowledge, learning outcomes are measured by effectiveness, efficiency, and attractiveness. Dwiyogo's research (2013, 2014, and 2015) developed a tuition design model that combines face-to-face schooling using offline resources (print, audio, video, computer) and online knowledge training (internet and smart phones) known as blended learning-based instruction design models. Numerous studies have been conducted to test the potency, capability, and fascination of learning. However, the objectives of this study with respect to Dwiyogo’s model are: (1) examining experts on its usage; (2) applying the model in courses; and (3) testing the productivity and capability. This research makes use of the survey and quasi-experimental design methods. The data consists of a total of 3 experts, 113 students, and 6 teachers, with the results showing that the blended learning model using eight items produced a huge output (= 4.750, SD = 0.361). Based on the components of the expert test, it can be concluded that the learning model developed is appropriate and can be implemented. Student opinion with respect to this model showed a high level of agreement (= 3.415, SD = 0.536). This shows that students who applied blended learning-based instruction models responded positively to its implementation. Therefore, this technique can enhance knowledge, thereby making the act of efficient, effective, and instructive appeal.